The Baltic Psalteries: Bibliographical Problems and Desiderata Revisited - Carl Rahkonen (Suomen Etnomusikologisen Seura [Finnish Ethnomusicological Society], 2009)
This article describes the scholarly literature pertaining to the Baltic psalteries, instruments played in Finland, Estonia, Latvia, Lithuania and the Karelian part of Russia. It is an update of a seminal article on Baltic psaltery bibliography done by Stephen Reynolds in 1973. Since that time, communication among scholars has increased greatly, especially after the arrival of the internet. There have been several international Baltic psaltery symposia. Even with these advances, many challenges remain in discovering, obtaining, and studying scholarly Baltic psaltery literature. The article includes a selected bibliography of significant studies up to 2009.